RATE OF MALIGNANT BREAST CANCER AMONG WOMEN WITH BREAST MASS ATTENDING ALDEWANIYAH TEACHING HOSPITALS: A CROSS-SECTIONAL STUDY - Jallab, Hassan Raji (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The problems of breast mass, pain, or discharge are extremely common in the Iraqi population, as well as, globally. However, the trend in most health-care institutions is that most breast lesions are of benign biologic behavior and among true neoplastic lesions. Marital status has been linked to the outcome of breast malignancy; however, the link is controversial.Thus, the aim of the present study is to make a clear insight into the true incidence rate of carcinoma and their risk factors. Materials and Methods: The study was designed to be a cross-sectional study involving a cohort of 182 Iraqi women with the breast mass. Patients were selected in a systemic random way from the population of patients already visiting the surgical consultation clinic and ward and oncology unit in Al-Dewaniyah teaching hospital in Al-Diwaniyah province, Iraq. Result: The present study showed that the most breast lesions (82%) were benign, and the most frequent one was a fibroadenoma (37.4%). Malignant lesions accounted for a small percentage (17.4%). Mean age of patients with carcinoma was 49.78Â±7.58 years and most all cases occurred after 20 years of age and that 87.5% of cases were seen after the age of 40. Majority of breast carcinoma were of invasive ductal carcinoma. No significant association was seen between the clinical behavior of breast mass and marital status; however, malignant clinical behavior showed significant association with age. Conclusion: The incidence rate of malignant breast lesions in Iraqi women with breast mass is similar to that seen worldwide and that age is the main risk factor that predicts the malignant clinical behavior of a breast mass.